Safety of Laparoscopic Colorectal Surgery in a Low-Volume Setting: Review of Early and Late Outcome - Robert C. Gandy; Christophe R. Berney (Gastroenterology Research and Practice)
Background. There is increasing evidence suggesting that the laparoscopic technique is the treatment of choice for large bowel resection, including for malignancy. The purpose of the study was to assess whether general surgeons, with particular skills in advanced laparoscopy, can adequately provide safe laparoscopic colorectal resections in a low-volume setting. Methods. A retrospective review of prospectively collected case series of all laparoscopic colorectal resections performed under the care of a single general surgeon is presented. The primary endpoint was postoperative clinical outcome in terms of morbidity and mortality. Secondary endpoints were adequacy of surgical margins and number of lymph nodes harvested for colorectal cancer cases. Results. Seventy-three patients underwent 75 laparoscopic resections between March, 2003, and May, 2011. There was no elective mortality and the overall 30-day postoperative morbidity was 9.3%. Conversion and anastomotic leakage rates were both 1.3%, respectively. None of the malignant cases had positive margins and the median number of lymph nodes retrieved was 17. Conclusions. Our results support the view that general surgeons with advanced skills in minimally invasive surgery may safely perform laparoscopic colorectal resection in a low-volume setting in carefully selected patient cases.